2017
DOI: 10.3390/ijms18081664
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Galectin-3 Blockade in Vascular and Aortic Valve Alterations in an Experimental Pressure Overload Model

Abstract: Galectin-3 (Gal-3) is involved in cardiovascular fibrosis and aortic valve (AV) calcification. We hypothesized that Gal-3 pharmacological inhibition with modified citrus pectin (MCP) could reduce aortic and AV remodeling in normotensive rats with pressure overload (PO). Six weeks after aortic constriction, vascular Gal-3 expression was up-regulated in male Wistar rats. Gal-3 overexpression was accompanied by an increase in the aortic media layer thickness, enhanced total collagen, and augmented expression of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
(59 reference statements)
2
18
0
Order By: Relevance
“…43 Nonetheless, experimental models suggest that blocking Gal-3 pathways may attenuate cardiac fibrosis, vascular remodelling, LV dysfunction, and heart failure onset. 44,45 In this study, higher Gal-3 levels were associated with lower lateral e 0 and septal e 0 , suggesting that Gal-3 may also be related to DD independently of increased congestion. 46,47 Reduced systemic concentrations of ICTP may reflect reduced collagen type I fibre degradation by MMP-1 given that high lysyl oxidase-mediated cross-linking increases the resistance of the fibre to MMP-1 proteolysis.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…43 Nonetheless, experimental models suggest that blocking Gal-3 pathways may attenuate cardiac fibrosis, vascular remodelling, LV dysfunction, and heart failure onset. 44,45 In this study, higher Gal-3 levels were associated with lower lateral e 0 and septal e 0 , suggesting that Gal-3 may also be related to DD independently of increased congestion. 46,47 Reduced systemic concentrations of ICTP may reflect reduced collagen type I fibre degradation by MMP-1 given that high lysyl oxidase-mediated cross-linking increases the resistance of the fibre to MMP-1 proteolysis.…”
Section: Discussionsupporting
confidence: 50%
“…fibroblasts, macrophages, myocytes, and renal cells) and may be extracellular, cytoplasmic, or nuclear. 44,45 In this study, higher Gal-3 levels were associated with lower lateral e 0 and septal e 0 , suggesting that Gal-3 may also be related to DD independently of increased congestion. 43 Nonetheless, experimental models suggest that blocking Gal-3 pathways may attenuate cardiac fibrosis, vascular remodelling, LV dysfunction, and heart failure onset.…”
Section: Discussionsupporting
confidence: 49%
“…In a recent study, it has been demonstrated that pharmacological Gal-3 inhibition by MCP could delay vascular remodeling and inflammation in a rat model of pressure overload (Fig. 3) 51,56 . Gal-3 inhibition exerts beneficial effects, decreasing aortic tunica media hypertrophy.…”
Section: Beneficial Effects Of Galectin-3 Blockade On Vascular Alteramentioning
confidence: 98%
“…Complementarily, MCP treatment diminishes the expression of the inflammatory markers interleukin-6, interleukin-1β, tumor necrosis factor-α, monocyte chemoattractant protein-1, osteopontin, cd45 and cd68 in pressure-overloaded aortae (Fig. 3) 51,56 . These results suggest that Gal-3 may contribute toward adverse cardiovascular effects in part through an effect on aortic stiffness.…”
Section: Beneficial Effects Of Galectin-3 Blockade On Vascular Alteramentioning
confidence: 98%
See 1 more Smart Citation